English for Communication: Strengthening English Language Skills for Students at Pesantren Mahasiswa Darushohabah Jakarta - Gufron, Gufron (IKRA-ITH ABDIMAS, 2025)
This community service initiative (PkM) addressed the critical need for English communication skills among students at Pesantren Mahasiswa Darushohabah in Jakarta. Recognizing English proficiency as an essential global competency, the program targeted persistent challenges in oral communication faced by pesantren students (Santri) due to limited practice opportunities and confidence issues. The "English for Communication" seminar employed Communicative Language Teaching (CLT) methods, combining motivational lectures with practical speaking exercises including role-plays, simulations, and interactive discussions. Fifteen participants engaged in 2 hours of intensive training focusing on daily communication scenarios, strategies for improving speaking skills, and confidence-building techniques. Pre-activity observations revealed students' initial reluctance and anxiety about speaking English, particularly in formal settings. However, post-activity evaluations demonstrated significant improvement in participation levels, with 80% of attendees actively engaging in conversation exercises by the session's conclusion. Qualitative feedback highlighted increased motivation and reduced speaking anxiety among participants, who particularly valued the non-judgmental learning environment. The program successfully achieved its dual objectives of enhancing practical communication skills and fostering self-efficacy, as evidenced by participants' requests for ongoing English clubs and additional learning materials. This intervention demonstrates the effectiveness of CLT approaches in religious educational contexts and underscores the importance of creating supportive environments for language practice. Recommendations include establishing regular speaking sessions and developing contextual learning resources to sustain the program's impact.